2019
DOI: 10.2139/ssrn.3358187
|View full text |Cite
|
Sign up to set email alerts
|

Hand Sign to Bangla Speech: A Deep Learning in Vision Based System for Recognizing Hand Sign Digits and Generating Bangla Speech

Abstract: Recent advancements in the field of computer vision with the help of deep neural networks have led us to explore and develop many existing challenges that were once unattended due to the lack of necessary technologies. Hand Sign/Gesture Recognition is one of the significant areas where the deep neural network is making a substantial impact. In the last few years, a large number of researches has been conducted to recognize hand signs and hand gestures, which we aim to extend to our mother-tongue, Bangla (also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…However, Hu et al had developed a suggestion for the design of hybrid CNN and RNN to preserve the temporal features correctly for the electromyogram signal, which addresses the issue of action identification. Another work [26] describes an extraordinary CNN model that automatically detects numbers relying on hand signals and communicates the specific outcome in the Bangla language, which is followed in this study. In a similar work [27], a CRNN module for hand pose estimation is conducted.…”
Section: Related Workmentioning
confidence: 99%
“…However, Hu et al had developed a suggestion for the design of hybrid CNN and RNN to preserve the temporal features correctly for the electromyogram signal, which addresses the issue of action identification. Another work [26] describes an extraordinary CNN model that automatically detects numbers relying on hand signals and communicates the specific outcome in the Bangla language, which is followed in this study. In a similar work [27], a CRNN module for hand pose estimation is conducted.…”
Section: Related Workmentioning
confidence: 99%
“…We implemented rotation testing cases with the systems Fig. 7: Comparative analysis of each system's accuracy for rotated images [5], [14]- [17] for testing their system. From the graph we identified that system [17] works poorly for rotated images.…”
Section: Test Case-1 Rotationmentioning
confidence: 99%
“…If we got 100 converted images from the input, then the concept is clear getting lots of images from a sample image. From the graph we identified that system [17] works poorly for contrasted images.…”
Section: Test Case-2 Contrastmentioning
confidence: 99%
See 2 more Smart Citations